Africa's Trade Revisted - Tamirisa, Natalia (IMF Working Papers; Working Paper ;, 2001)
The popular impression that Africa has not integrated into world trade, as suggested by the evolution in simple indicators, has been called into question recently by more formal analysis. This paper refines and generalizes this analysis, but lends support to the popular view of disintegration. Africa, especially Francophone Africa, is currently under-exploiting its trading opportunities and has witnessed disintegration over time, a trend that is most pronounced in its trade with the technologically advanced countries.